The Blackwell companion to nineteenth-century theology - Fergusson, David (Blackwell companions to religion, 2010)
Bringing together a collection of essays by prominent scholars, this book presents a comprehensive account of the most significant theological figures, movements, and developments of thought that emerged in Europe and America during the 19th century